The visceral pancreatic neck anterior distance may be an effective parameter to predict post-pancreaticoduodenectomy clinically relevant postoperative pancreatic fistula. Issue 2 (February 2023) - Zhao, Zhirong; Zhou, Lichen; Han, Li; Zhou, Shibo; Tan, Zhen; Dai, Ruiwu
Abstract: Background: The clinically relevant postoperative pancreatic fistula (CR-POPF) is significantly correlated with a high post-pancreaticoduodenectomy (PD) mortality rate. Several studies have reported an association between visceral obesity and CR-POPF. Nevertheless, there are many technical difficulties and controversies in the measurement of visceral fat. The aim of this research was to determine whether the visceral pancreatic neck anterior distance (V-PNAD) was a credible predictor for CR-POPF. Methods: We retrospectively analyzed the data of 216 patients who underwent PD in our center between January 2016 and August 2021. The correlation of patients' demographic information, imaging variables, and intraoperative data with CR-POPF was assessed. Furthermore, areas under the receiver operating characteristic curves for six distances (abdominal thickness, visceral thickness, abdominal width, visceral width, abdominal PNAD, V-PNAD) were used to identify the best imaging distance to predict POPF. Results: In the multivariate logistic analysis, V-PNAD ( P  < 0.01) was the most significant risk factor for CR-POPF after PD. Males with a V-PNAD >3.97 cm or females with a V-PNAD >3.66 cm were included into the high-risk group. The high-risk group had a higher prevalence of CR-POPF (6.5% vs. 45.1%, P  < 0.001), intraperitoneal infection (1.9% vs. 23.9%, P  < 0.001), pulmonary infection (3.7% vs. 14.1%, P  = 0.012), pleural effusion (17.8% vs. 33.8%, P  = 0.014), and ascites (22.4% vs. 40.8%, P  = 0.009) than the low-risk group. Conclusion: Of all imaging distances, V-PNAD may be the most effective predictor of CR-POPF. Moreover, high-risk patients (males, V-PNAD >3.97 cm; females, V-PNAD >3.66 cm) have a high incidence of CR-POPF and poor short-term post-PD prognosis. Therefore, surgeons should perform PD carefully and take adequate preventive measures to reduce the incidence of pancreatic fistula when the patient has a high V-PNAD.